Human Rights in The Context of Globalization - Tchinaryan, Elena Olegovna (2020)
Globalization as a phenomenon, being universal by its nature and character, covers not only the global economy, finance, and mass media, where it manifests itself in the most developed form, but also in other spheres of social life, including law. At the same time, the impact of global factors significantly affects the essential and substantive aspects of the state's legal system. The article deals with such concepts as globalization, unification, and universalization in the context of human rights theory. The universal culture of human rights is based on the universalization of the idea of human rights and the universal recognition of such values as human dignity, freedom, and responsibility. The development of human rights is considered as a social phenomenon included in the general dynamics of social processes. First of all, the influence of globalization on human rights in the context of intensively developing states and the rights and methods of intercultural dialogue are studied. The formation of a universal culture of human rights depends on the extent to which the idea of human rights and its values, enshrined in international standards and implemented in the national legislation of states, are perceived and reinterpreted in local cultures. An important feature of the modern system of human rights protection is the fact that, at the early stages, the formation of protective mechanisms occurred under the influence of national (domestic) characteristics of a state. However, since the middle of the 20th century, global factors have had a significant impact on this process. A study on the problem of methodological substantiation of the human rights concept in modern conditions of social development is presented in the article.